Heat transfer and friction loss analysis of non-wood fiber suspensions in closed conduit flow / Samira Gharehkhani - Samira , Gharehkhani (2016)
Study of the behavior of pulp fiber suspension flow is one of the most significant scientific interests as addition of small amount of fiber to the water changes the flow behavior considerably. Pulp and paper mills are the major industries using the fiber suspensions. However, the tendency of using non-wood fibers as one of the alternative sources is going to be increased, the lack of knowledge about the non-wood fiber suspension flow in pipe raised some concerns regarding the handle of non-wood pulp suspension in different processes. There is no significant reporting about non- wood pulp suspension flow in the pipelines. Therefore, the investigation of the non-wood fiber suspension in pipe flow, such as heat transfer and pressure drop trends seem necessary to obtain. A set up was built in order to evaluate the heat transfer and pressure drop characteristics of flowing pulp fiber suspensions. A number of experiments were conducted for different types of non-wood pulp fibers (Kenaf, Rice straw and Empty fruit bunches fibers). The results show that most of the fiber and paper properties could be correlated with both hc and pressure drop data. Using this strategy, the papermakers can predict and monitor the paper quality at the stock delivery step (delivery pipe). In order to investigate another objective of this study, a series of experiments were performed to examine the effect of presence of additives e.g. cationic polyacrylamide (CPAM), potato starch and nanocrystalline cellulose (NCC) in pulp suspension on pressure loss and drag reduction phenomena. Among these polymers the hydrodynamic behavior of NCC as a new generation of additives is less known and there is no any report on pipe flow behavior of NCC/pulp mixture. The results revealed that the pulp mixture containing 150 ppm NCC produced higher drag reduction level than pulp suspension alone. The findings in present work can shed light on flow mechanism of non-wood fibers suspensions and their mixtures with polymers in pipe flow.